Pemetaan Profil Kecerdasan Majemuk Generasi Z sebagai Dasar Perancangan Pembelajaran - Yoga Prismanata (Universitas Negeri Yogyakarta, 2026)
Multiple intelligences provide an overview of the variety of intelligence possessed by an individual, so that it can identify and analyze the characteristics of students. These student characteristics can be a reference for educators in determining the appropriate learning design, especially in differentiated learning. This study aims to map the profile of multiple intelligences possessed by Generation Z. The method used in this study is quantitative descriptive. Quantitative descriptive research is one type of research that aims to describe systematically, factually, and accurately the facts and characteristics of a particular population. Data collection was obtained from 950 high school students and students who are Generation Z respondents using a multiple intelligence instrument. The results of the study show that Generation Z has a percentage score of linguistic intelligence of 33%, logical-mathematical intelligence of 63%, visual-spatial intelligence of 65%, kinesthetic intelligence of 55%, musical intelligence of 72%, intrapersonal intelligence of 68%, interpersonal intelligence of 73%, naturalist intelligence of 59%, and existential intelligence of 76%. Generation Z has dominant intelligence in the form of existential, interpersonal, and musical intelligence. Mapping multiple intelligence profiles helps educators to determine the right learning design for Generation Z.